A thermoelectric generator using loop heat pipe and design match for maximum-power generation. (5th December 2015) - Huang, Bin-Juine; Hsu, Po-Chien; Tsai, Rung-Je; Hussain, Muhammad Mustafa
Abstract: The present study focuses on the thermoelectric generator (TEG) using loop heat pipe (LHP) and design match for maximum-power generation. The TEG uses loop heat pipe, a passive cooling device, to dissipate heat without consuming power and free of noise. The experiments for a TEG with 4 W rated power show that the LHP performs very well with overall thermal resistance 0.35 K W −1, from the cold side of TEG module to the ambient. The LHP is able to dissipate heat up to 110 W and is maintenance free. The TEG design match for maximum-power generation, called "near maximum-power point operation (nMPPO)", is studied to eliminate the MPPT (maximum-power point tracking controller). nMPPO is simply a system design which properly matches the output voltage of TEG with the battery. It is experimentally shown that TEG using design match for maximum-power generation (nMPPO) performs better than TEG with MPPT. Highlights: We develop thermoelectric generator (TEG) using loop heat pipe and design for maximum power. TEG uses loop heat pipe to dissipate heat without consuming power and free of noise. TEG using design match for maximum-power generation performs better than TEG with MPPT.